International investment agreements and public health: neutralizing a threat through treaty drafting - Bryan Mercurio
The high profile investment claims filed by Philip Morris challenging Uruguayan and Australian measures that restrict advertising and logos on tobacco packaging awakened the public health community to the existence and potential detrimental impact of international investment agreements (IIAs). More recently, Eli Lilly challenged Canada's invalidation of a pharmaceutical patent under an IIA. All of the cases claim that the intellectual property rights of the investor were infringed. As a result of these cases, many commentators and activists view IIAs as a threat to public health and have lobbied against their inclusion in ongoing trade negotiations. This article does not argue against IIAs. Instead, it seeks to demonstrate how more sophisticated treaty drafting can neutralize the threat to public health. In this regard, the article seeks to engage members of the public health community as campaigners not against IIAs but as advocates of better treaty drafting to ensure that IIAs do not infringe upon the right of a nation to take non-discriminatory measures for the promotion and protection of the health of their populations.